Optimal Pricing Strategy for Telecom Operator in Cellular Networks with Random Topologies - Liu, Gexian; Zhao, Liqiang; Shang, Bodong; Chu, Xiaoli; Chen, Kwang-Cheng (2018 IEEE International Conference on Communications (ICC), 2018)
Traditional pricing of a cellular network operator considers the bandwidth utilization for users and operational cost. In this paper, we re-examine this critical subject through a holistic engineering view taken energy efficiency into account. We treat this issue as a two-stage Stackelberg game between the operator and mobile users, where the operator determines the price of unit bandwidth, and accordingly the users choose the amount of requested bandwidth to maximize their payoff. To reach a general result, randomly deployed base stations in large scale have been taken into consideration. By stochastic geometry, we derive the operator's profit and the energy efficiency per unit area, while considering the actual bandwidth demand of users based on their acceptable price. Simulation results show that the operator's profit and the energy efficiency can be achieved their maximum at nearly the same price (i.e., optimal price), and the optimal pricing strategy varies with the deployment density of base stations.